Water and sediment toxicity in a river affected by former mining residues - Moledo de Souza Abessa, Denis; Gonçalves Morais, Lucas; Perina, Fernando Cesar; Bergo Davanso, Marcela; Moreira Buruaem, Lucas; Manólio de Paula Martins, Letícia; Barbujiani Sígolo, Joel; Guimarães Silvestre Rodrigues, Valéria (O Mundo da Saúde, 2012)
The Ribeira de Iguape River basin received intense mining activities for lead exploiting and, as a result, the river received the discharges of estimated amounts of 5.5 tons/month of material rich in As, Ba, Cd, Pb, Cu, Cr and Zn. In this article, the toxicity of waters and sediments collected in Ribeira de Iguape River was assessed aiming to estimate environmental quality. Three sampling campaigns were conducted, from 2009 to 2010. Toxicity tests with the cladoceran Daphnia similis were done for water samples and for sediments, in this case using sediment-water interface exposure. Results showed in general absence of toxicity for sediments and waters, and only eventually were acute effects registered (marginal toxicity). Results are consistent with the conditions indicated by the literature, of low concentrations of metals in waters and sediments; however they differ from the monitoring made by the state environmental agency, which registered chronic toxicity. The occurrence of eventual acute toxicity indicates that although Ribeira de Iguape River quality is being restored, conditions still are not totally under control.